Research Review: Multi‐informant integration in child and adolescent psychopathology diagnosis. (5th August 2016) - Martel, Michelle M.; Markon, Kristian; Smith, Gregory T.
Abstract : Background: An empirically based, clinically usable approach to cross‐informant integration in clinical assessment is needed. Although the importance of this ongoing issue is becoming increasingly recognized, little in the way of solid recommendations is currently provided to researchers and clinicians seeking to incorporate multiple informant reports in diagnosis of child psychopathology. The issue is timely because recent developments have created new opportunities for improved handling of this problem. For example, advanced theories of psychopathology and normal and abnormal child development provide theoretical guidance for how integration of multiple informants should be handled for specific disorders and at particular ages. In addition, more sophisticated data analytic approaches are now available, including advanced latent variable models, which allow for complex measurement approaches with consideration of measurement invariance. Findings: The increasing availability and mobility of computing devices suggests that it will be increasingly feasible for clinicians to implement more advanced methods rather than being confined to the easily memorized algorithms of the DSM system. Conclusions: Development of models of cross‐informant integration for individual disorders based on theory and tests of the incremental validity of more sophisticated cross‐informant integration approaches in comparison to external validation criteria (e.g. longitudinal trajectories and outcomes, treatment response, and behavior genetic etiology) should be a focus of future work.